Navigating the evolved FMCG loyalty frontier: Subscription loyalty models within the Western Cape, South Africa. - Santana, Emmanuel Louis (The IIE, 2025)
Although loyalty programmes are now commonplace, their prevalence has diminished critical reflection on what genuinely sustains loyalty beyond repetitive behaviour. Over a decade ago, more than two billion loyalty programmes existed in the United States, illustrating the global saturation of reward systems. Within this crowded landscape, this research investigates Checkers’ Xtra Savings Plus, South Africa’s leading FMCG subscription-based loyalty programme, where access to value is conditional upon payment and continued participation. Over one hundred loyalty-oriented studies spanning eighty years were synthesised to identify thirteen constructs central to loyalty development. These constructs informed a proprietary conceptual model and scale instrument, applied to a Western Cape sample of 134 respondents and bootstrapped to 5 000 for statistical reliability. Using descriptive statistics, exploratory factor analysis, and Monte Carlo parallel analysis, the model refined into four operational constructs: Customer Loyalty, Perceived Programme Value, Brand Loyalty, and True Loyalty. An inferential factor analysis revealed that Customer Loyalty demonstrated 53% explanatory power on Perceived Programme Value, which exerted 50% on Brand Loyalty, which held 51% on Subscription Utility, which in turn possessed 58.6% explanatory power on True Loyalty. Subscription Utility achieved a loading of 96.8%. This framework empirically confirms that loyalty’s endurance arises from the interdependence of value clarity, behavioural consistency, and relational trust. Subscription Utility is newly introduced and repositions usefulness from an abstract promise into an in-use experience co-produced by these three antecedents. Perceived value without routine provides little durability; routine without value erodes credibility; and brand affinity without either, collapses under price pressure. True Loyalty therefore emerges only when all three mechanisms converge in harmony, transforming a reward system into a unified experience of meaning, reliability, and reciprocity. Further research is encouraged to interrogate the remaining 41% of variance that influences True Loyalty, particularly factors beyond economic value that may drive long-term consumer attachment.
Keywords: Customer loyalty; Brand loyalty; Retail; Subscription programmes